2012
DOI: 10.1056/nejmoa1205127
|View full text |Cite
|
Sign up to set email alerts
|

Ponatinib in Refractory Philadelphia Chromosome–Positive Leukemias

Abstract: Background Resistance to tyrosine kinase inhibitors in patients with chronic myeloid leukemia (CML) and Philadelphia chromosome–positive acute lymphoblastic leukemia (Ph-positive ALL) is frequently caused by mutations in the BCR-ABL kinase domain. Ponatinib (AP24534) is a potent oral tyrosine kinase inhibitor that blocks native and mutated BCR-ABL, including the gatekeeper mutant T315I, which is uniformly resistant to tyrosine kinase inhibitors. Methods In this phase 1 dose-escalation study, we enrolled 81 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
548
2
19

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 685 publications
(574 citation statements)
references
References 42 publications
5
548
2
19
Order By: Relevance
“…Considering the present findings and the approval of ponatinib by FDA for the treatment of refractory patients with chronic myelogenous leukemia (19), a clinical trial of ponatinib for systemic mastocytosis patients with D816V KIT mutation may be warranted.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Considering the present findings and the approval of ponatinib by FDA for the treatment of refractory patients with chronic myelogenous leukemia (19), a clinical trial of ponatinib for systemic mastocytosis patients with D816V KIT mutation may be warranted.…”
Section: Discussionmentioning
confidence: 91%
“…Ponatinib (AP24534), a potent multitargeted kinase inhibitor (18), has been approved by the FDA for treating imatinib-resistant patients with chronic myelogenous leukemia, including those harboring the gatekeeper mutant T315I Bcr-Abl (19,20). Besides, ponatinib also manifests inhibitory activity toward PDGFR, KIT, as well as FGFR (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Ponatinib, one of the third-generation TKIs, is known to be effective in CML patients even bearing T315I mutation because of its capability to bind to BCR/ABL kinase. In a phase I clinical trial, it has been reported that ponatinib treatment of CML patients with T315I mutation results in hematological response in all of the patients, complete cytogenetic response (CCyR) in 75 % of the patients, and also major molecular response (MMR) in 67 % of the patients [33]. A phase II international clinical study, Ponatinib Ph+ ALL and CML Evaluation (PACE), has reported that CCyR is seen in 46 % of CML patients with T315I mutation [34].…”
Section: Discussionmentioning
confidence: 99%
“…Minami Y, et al reported that monitoring gene mutations in fractionated hematopoietic stem cells and progenitors at diagnosis may help detect the T315I mutation earlier [38]. Standard methods to detect the T315I mutation and the standard management of patients with this mutation in practice need to be established [28,39,40].…”
Section: Discussionmentioning
confidence: 99%